Transformations and functional role of starch during potato crisp making: A review. Issue 12 (6th November 2020) - Reyniers, Stijn; Ooms, Nand; Delcour, Jan A.
Abstract: Potato chips are a major product in the savory snack market and are consumed worldwide because of their enjoyable and distinctive organoleptic properties. They are conventionally produced by deep‐frying thin slices of fresh potato. In contrast, potato crisps are manufactured from dried potato derivatives such as potato flakes (PFs). Their production is reviewed in this manuscript and requires the formation of dough based on hydrated PFs. Expansion of the dough during deep‐frying provides the crisps with their desired crunchy texture. As part of an overall trend, the consumer search for calorie‐reduced food products has also stimulated research to lower oil uptake during crisp production. However, minimizing oil absorption without losing the characteristic palatability of deep‐fried products is challenging and requires fundamental knowledge on factors determining product texture and oil absorption. The transformations and functional role of starch, potato's main constituent, during crisp making are key in this respect and are reviewed here.